2013
DOI: 10.1007/s12192-012-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

Hsps are up-regulated in melanoma tissue and correlate with patient clinical parameters

Abstract: Heat shock proteins (hsps) have been studied in numerous cancer types, but a clear view of their clinical relevance in melanoma remains elusive. Therefore, the aim of this study was to investigate the expression of hsps in melanoma with respect to patient clinical parameters. Using Western immunoblotting, hsps 90, 70, 60, 40 and 32 were observed to be widely expressed in metastatic melanomas (n031), while immunofluorescence demonstrated that in the majority of samples these hsps, apart from hsp32, were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…While HSP90 level is low in benign melanocytic nevi, it increases during melanoma progression [36]. Consequently, a high level of HSP90 was assessed in more than 50% of melanoma tumors [37,38]. Although high HSP90 expression is not a predictive factor for patient survival, HSP90 level significantly correlated with the Clark level and increased Breslow depth in primary melanomas [36].…”
Section: Hsp90 In Melanomamentioning
confidence: 99%
“…While HSP90 level is low in benign melanocytic nevi, it increases during melanoma progression [36]. Consequently, a high level of HSP90 was assessed in more than 50% of melanoma tumors [37,38]. Although high HSP90 expression is not a predictive factor for patient survival, HSP90 level significantly correlated with the Clark level and increased Breslow depth in primary melanomas [36].…”
Section: Hsp90 In Melanomamentioning
confidence: 99%
“…Moreover, the relevant role that chaperones (for example; HSP70, HSP90) play in preserving melanoma survival and plasticity is emphasized by their correlation with disease progression (103, 104) and the manifested vulnerability that melanoma cells exhibit following perturbations of global proteostasis. A study comparing the expression levels of HSPs across patient clinical parameters showed that, with the notable exception of HSP32, whose expression correlated with improved patient survival, increased expression of HSP90 and HSP40 correlated with advanced stages of melanoma, and in the case of HSP40 with decreased patient survival (105). In line with this, another study observed an indispensable role of HSF1 in melanoma progression and migration, thus highlighting its potential as therapeutic target in melanoma (106).…”
Section: Adapt and Survive: Alteration Of Cytoplasmic And Upr-based Pmentioning
confidence: 99%
“…By inhibiting Hsp90, 17-AAG causes the destabilization of the products of several mutant oncogenes, including BRAF, CRAF and NRAS [17] . Through its role in regulating the conformation, stability and function of several key oncogenic client proteins, Hsp90 is essential in maintaining malignant transformation and in increasing the survival, growth, and invasive potential of cancer cells, including melanomas [18] [19] . Several members of this drug class have been tested in human clinical trials [20] , and while the drugs may slow tumor growth, to date none have succeeded as single agents [21] .…”
Section: Introductionmentioning
confidence: 99%